The Evolutionary and Molecular impacts on Human Genetics; Review: The Human Genome Evolution (European journal of volunteering and community-based projects, 2021)
The human genome holds a record of the evolutionary forces that have shaped our species. In human genome evolution, DNA sequences-genomics analysis, molecular-based analysis, population genetics, molecular genetics, functional genomics, genome function identification/profiling, and genomics modeling, and simulation have deepened our understanding of human genome evolutionary history, natural selection, and other studies. We study, some factors that influence the evolution of the human genome are the functional modification of DNA, post-translational modification (PTM), gene regulation, analysis of chromatin conservation, modification of histone, structural variations, mutational biases, single nucleotide polymorphism (SNPs) and gene-phenotypes interaction along the genome. By using the natural selection and evolutionary theory as study, these some phenomena will play a vital role in the understanding of the human genome and also breakthroughs in in-vivo and in-silico studies.